Expression profiles and potential clinical significance of circular RNAs in peripheral neutrophils of patients with intracranial atherosclerotic stenosis - Ziping Han; Tao Wang; Lingzhi Li; Junfen Fan; Rongliang Wang; Yangmin Zheng; Feng Yan; Haiping Zhao; Yumin Luo; Liqun Jiao (Brain Circulation)
BACKGROUND: Expression profiles and clinical significance of circular RNAs (circRNAs) in intracranial atherosclerotic stenosis (ICAS) patients have not been investigated yet. MATERIALS AND METHODS: A circRNA microarray was employed to identify differentially expressed circRNAs (DEcircRNAs) in peripheral neutrophils of ICAS patients. The levels of upregulated hsa-circRNA-087631/hsa-circRNA-101141 and downregulated hsa-circRNA-100914/hsa-circRNA-001082 were verified using quantitative real-time polymerase chain reaction (qRT-PCR). In addition, we compared the levels of those four DEcircRNAs before endovascular treatment (pre-E) and 24 h after endovascular treatment (post-E) and between patients with adverse event and severe adverse event (AE/SAE) and those without. Their area under the curve from the receiver operating characteristic (ROC) curve was calculated as well. Bioinformatic analyses of DEcircRNAs host genes and targeted genes in DEcircRNA-miRNA-mRNA regulatory network were further performed. RESULTS: A total of 70 circRNAs were identified as differentially expressed in patients with ICAS; of these, 7 were upregulated and 63 were downregulated. qRT-PCR-based validation results of the four DEcircRNAs corresponded with the microarray data. The upregulated hsa-circRNA-087631 and hsa-circRNA-101141 were significantly downregulated 24 h post-E; moreover, they were significantly increased in patients with perioperative AE/SAE compared to those without AE/SAE. ROC analysis further supported their potential to be exploited as diagnostic biomarkers for ICAS. The validated DEcircRNA-miRNA-mRNA regulatory network and further bioinformatic analysis supported the core roles of hsa-circRNA-101141 in regulating target genes mainly related to actin or microtubule-based process. CONCLUSIONS: DEcircRNAs in peripheral neutrophils could serve as biomarkers for the diagnostic and AE prediction in ICAS patients receiving endovascular treatment. Moreover, these DEcircRNAs, especially hsa-circRNA-101141-hsa-miRNA-181d axis, might participate in the pathogenesis of ICAS by acting on actin or microtubule-based cytoskeleton organization processes in neutrophils. TRIAL REGISTRATION: The CRTICAS study has been registered previously in the ClinicalTrial.gov database (NCT01994161).